PERENCANAAN STRATEGIS SISTEM INFORMASI PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT PENGUMPUL MENENGAH DI KALIMANTAN BARAT DENGAN MENGGGUNAKAN METODE WARD AND PEPPARD - M.Qadafi Khairuzzaman (Jurnal Khatulistiwa Informatika, 2015)
Research on Oil Palm Gatherers In West Kalimantan, which aims to analyze the company's business areas, making the information to make strategic enterprise information systems become more effective and efficient and can compete with its peers. In this study, using a form of case study and the methods used in this study was Ward and Peppard. The data collection techniques used were interviews, observation and documentation. Analysis tools that I use in getting internal and external analysis of the company is a SWOT Analysis, Value Chain Analysis, Analysis Porter's Five Competitive Power. Results obtained from strategic planning of information systems in Palm Oil Gatherer In West Kalimantan produces useful information system to integrate information on internal and external processes, so that the working procedure becomes easier, focused, clear, and information can be obtained more quickly, precise and accurate. The information on the intention is that the information is a strategy based on the target company's business as the development of information systems towards achieving a competitive advantage for the company.Keywords: Strategic Planning Information Systems, Methods Ward and Peppard, Palm Oil Gatherer In West Kalimantan